Islamic capital markets : theory and practice - Krichene, Noureddine (Wiley Finance, 2013)
A comprehensive look at the essentials of Islamic capital markets Bringing together theoretical and practical aspects of capital markets, Islamic Capital Markets offers readers a comprehensive insight into the institutions, instruments, and regulatory framework that comprise Islamic capital markets